HUBUNGAN KESEIMBANGAN DAN KEKUATAN OTOT LENGAN DENGAN HASIL LEMPAR CAKRAM PADA SISWA KELAS VII MTS AL YAKIN PUNGPUNGAN - Wahyu Setia Kuscahyaning Putri; Nawafila Februyani; M. Choyim Al Amin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2016)
The background of this research is the presence of eighth grade students of MTs Al Yakin Pungpungan who have difficulty in throwing discs, and the problem is whether there is a relationship between balance and strength of arm muscleswith discus throwing and whether discus throwing is influenced by balance and strength of arm muscles. Therefore this study aims to determine the relationship of balance and arm muscle strength with discus throwing results in grade VII students of MTs Al Yakin Pungpungan in the 2018 school year. This research is a correlational study. The method used is a survey method and uses test and measurement techniques. Analysis of research data uses partial correlation and multiple regression. The population of this research is VII grade students of Al Yakin Pungpungan MTs in the 2018 school year with a total of 37 students. The instruments used were standing balance, push dynamometer and disc throwing test with stages from initial attitude to final throw attitude. The results of this study indicate that there is a significant relationship between balance and arm muscle strength with discus throwing results because r count = 0.369> r (0.05) (37) = 0.334. There is a significant relationship between balance with discus throwing because r count = 0.578> r (0.05) (37) = 0.334 and there is a significant relationship between arm muscle strength and discus throwing because Rhitung = 0.876> R (0.05) (37) ) = 0.334. The effective contribution of arm muscle strength by 26.6%, the ability of balance 50.2%, and the total effective contribution of arm muscle strength and balance ability to the results of discus throwing by 76.8% while the remaining 23.2% is determined by other factors or variables not examined in this study.